A decrease in plant gain, namely CO2 stores, characterizes dysfunctional breathing whatever its subtype in children - Bokov, Plamen; Peiffer, Claudine; Gallego, Jorge; Pautrat, Jade; Matrot, Boris; Delclaux, Christophe (Frontiers in Physiology, 2023)
Background. Whether dysfunctional breathing (DB) subtype classification is useful remains undetermined. The hyperventilation provocation test (HVPT) is used to diagnose DB. This test begins with a 3-min phase of hyperventilation during which fractional end-tidal CO2 (FETCO2) decreases that could be an assessment of plant gain, which relies on CO2 stores. Our aim was to assess 1) whether the children suffering from different subtypes of DB exhibit decreased plant gain and 2) the relationships between HVPT characteristics and plant gain.Methods. We retrospectively selected 48 children (median age 13.5 years, 36 females, 12 males) who exhibited during a cardiopulmonary exercise test either alveolar hyperventilation (transcutaneous PCO2 < 30 mmHg, n = 6) or inappropriate hyperventilation (increased VE'/V'CO2 slope) without hypocapnia (n = 18) or dyspnea without hyperventilation (n = 18) compared to children exhibiting physiological breathlessness (dyspnea for sports only, n = 6). These children underwent tidal-breathing recording (ventilation and FETCO2 allowing the calculation of plant gain) and a HVPT.Results. The plant gain was significantly higher in the physiological group as compared to the dyspnea without hyperventilation group, p=0.024 and hyperventilation without hypocapnia group, p=0.008 (trend for the hyperventilation with hypocapnia group, p=0.078). The slope of linear decrease in FETCO2 during hyperventilation was significantly more negative in physiological breathlessness group as compared to hyperventilation without hypocapnia group (p=0.005) and dyspnea without hyperventilation group (p=0.049).The children with DB, regardless of their subtype, deplete their CO2 stores (decreased plant gain), which may be due to intermittent alveolar hyperventilation, suggesting the futility of our subtype classification.